Governmental Local Investment Fund as a Financial Instrument to Support Urban Investment by the Example of Cities with District Status in the Lodz Voivodeship - Hajdys, Dagmara (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis is to present the Government’s Local Investment Fund as a financial tool to support municipalities and districts during the COVID-19 pandemic crisis and to provide an assessment of the support received in the context of investment expenditure incurred by cities with district rights in the Lodz Voivodeship. Methodology: On the basis of data from the Chancellery of the Prime Minister and the financial reports of the Cities with a District Status, the amount of funding granted from the Government Local Investment Fund was reviewed. Based on data from the Local Data Bank, the basic financial data for three Cities with a District Status from the Lodz Voivodeship in the years 2019–2021 was analysed, i.e. in the context of the use of funds from the Government Local Investment Fund. Results of the research: Local government units during the COVID-19 pandemic had an opportunity to obtain financial support from the state budget for the implementation of investment tasks from the Government Local Investment Fund. A total amount of PLN 13 billion was allocated to local governments. The funds were distributed in three rounds using two different qualification methods: algorithm and competition mode. Cities with a District Status under the competition procedure received less support than other local governments, and there were even situations in which they were deprived of this support. The distribution and the amount of support awarded caused a lot of controversy at the same time highlighting a need for changes in the system of local finances.